Numerical Analysis of Sensitivity of SAW Structure to the Effect of Toxic Gases - Tomasz HEJCZYK; Tadeusz PUSTELNY; Bartlomiej WSZOŁEK; Wieslaw JAKUBIK; Erwin MACIAK (Archives of Acoustics, 2016)
The paper presents the results of numerical analysis of the SAW gas sensor in the steady and non-steady states. The effect of SAW velocity changes vs surface electrical conductivity of the sensing layer is predicted. The conductivity of the porous sensing layer above the piezoelectric waveguide depends on the profile of the diffused gas molecule concentration inside the layer. The Knudsen’s model of gas diffusion was used.